Dochody gminy z nieruchomości - Małkiewicz, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article contains the list of local communities' incomes from real estates and their division according to the way of incomes generated. In the next part of this article there will presented the analysis of empiric data referring to that subject on the of Czestochowa community basis. The sources the above mentioned community's incomes are the following: communal property, real estate, agricultural and forest taxes and direct grants from the state budget. The thesis will be culminated in the presentation of the analysis presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 518-525